Pengaruh Pelatihan Training Simulator dan Bridge Simulator terhadap Peningkatan Kompetensi Taruna Nautika sebelum Praktik Laut - Fajar Gumelar; Ryan Puby Sumarta; Filemon Filemon; Norvan Bagus Ramadhan (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2025)
The development of simulation technology has become a crucial element in modern maritime education. This study aims to examine the effect of training simulator and the availability of bridge simulator equipment on the competence of Nautical cadets at Sorong Merchant Marine Polytechnic prior to sea practice. A quantitative approach with multiple linear regression was used to analyze the relationship between the independent variables (training simulator and bridge simulator) and the dependent variable (cadet competence). Data were collected from 26 cadets through structured questionnaires using purposive sampling. The results indicate that both variables significantly affect cadet competence, with the bridge simulator having a more dominant impact. The regression model yielded a high coefficient of determination (R² = 0.998), meaning that 99.8% of the variance in cadet competence is explained by the two predictors. These findings reinforce the critical role of simulation-based training, especially bridge simulators, in developing technical skills, navigation ability, situational awareness, and decision-making. The study supports the IMO-STCW framework, which mandates simulation in maritime certification. As a result, maritime education institutions are recommended to strengthen investment in training and bridge simulator facilities and integrate simulation-based methods into the curriculum to improve graduate competence and global competitiveness.